Elderly patients are at high risk of night‐time admission to the intensive care unit following a rapid response team call. Issue 12 (December 2016) - Sundararajan, K.; Flabouris, A.; Thompson, C.; Seppelt, ,, I.; ,
Abstract : Previous studies have shown that elderly patients (age ≥65 years) are less likely to be admitted to the intensive care unit following a rapid response team call and have high hospital mortality rates. This study has shown that elderly patients have a significantly higher probability of being admitted to an intensive care unit following a rapid response team call at night than during the day. However, at no time are they at greater risk than younger patients of incomplete vital sign recording, a failure to escalate care for acute deterioration or mortality.